Distance metric for soft-decision decoding in non-Gaussian channels - Chuah, T.C. (2003)
A new distance metric for soft-decision decoding in impulsive noise is proposed. Results reveal that soft-decoders employing Euclidean distance as a decoding metric suffer two limitations: an increase in constraint-length leads to degraded performances; secondly, their performance is poorer than hard-decoders. Both limitations are ameliorated by the proposed distance metric.